PROPOSED MARKETING STRATEGY FOR KINTSUGI COFFEE TO INCREASE SALES AND CUSTOMER PURCHASE INTENTION - Alief Fulki Shiddiq, Muhamad
The increasingly fierce competition in the coffee shop industry requires companies to continue to increase their competitiveness in order to be able to respond to market needs. One of these business actors is Kintsugi, which is a coffee shop that not only sells coffee but various types of non-coffee drink products and also provides snacks and heavy meals. Founded in 2020 and it is difficult to have a reputation and credibility in the eyes of consumers. Based on preliminary research conducted by the author, it is known that Kintsugi has low customer purchase intentions. The purpose of this research is to find out what the current condition of Kintsugi is and design the right marketing strategy to increase Kintsugi sales. This research uses quantitative methods by analyzing customers using questionnaires and conducting hypothesis testing using SPSS software. The research sample was taken totaling 200 respondents using non-probabilistic sampling techniques with judgment sampling with the criteria of having purchased or visited the Kintsugi coffee shop. Then the classical assumption test and multiple linear analysis were carried out.